Ribosomes dance to a daily rhythm - Iyer-Bierhoff, Aishwarya Murali; Grummt, Ingrid (Trends in biochemical sciences, 2017)
Sinturel et al. demonstrate that feeding-fasting rhythms and light-dark cycles direct daily changes in liver mass and cell size. These feeding-fasting- and light-dark-driven diurnal fluctuations are controlled by an unconventional mechanism that affects ribosome assembly and protein levels during the active phase.